The effectiveness of campaign for women empowerment / Nurin Balqis Azlan and Nur Hazaleen Saad - Azlan, Nurin Balqis; Saad, Nur Hazaleen (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
Lack of confidence and low esteem has been a problem to women around the world. From the very beginning of Levi’s, they celebrate women all abilities, shape and style. This campaign is to appreciate ladies that already achieve certain goals and achievement in their life. Levi’s campaign also does not differentiate between gender, race, and age. Lévi’s can fit for everyone, not just for women but men to in celebration of International Women’s Day (March 8), Levi's launched a campaign paying tribute to strong female figures. It invites women to share their compelling stories to the world. This campaign taps into female changemakers who are making an impact without gender qualifiers that are implied such as the “female version of this” or they are good at that” for a woman” which downplays their roles. (Behind Levi’s I Shape My World Initiative, 2020). I Shape My World features stories of pure courage and grit by women who selflessly pass the baton of empowerment for generations to come. This brand initiative may seem to have a simple concept, but it is meant to bring women everywhere the full recognition they deserve.